HRHuman: tuning-free higher-resolution human image generation via template knowledge - Li, Ling (2025)
High-resolution human-centric image generation offers significant potential across various industries, such as entertainment, media, and fashion. Diffusion models for text-to-image generation have significantly improved the quality of human image synthesis. However, when scaling to higher resolutions (2K, 4K, and above), they often encounter issues such as object repetition and structural distortion, which appear especially unnatural in human images. To address these challenges, we propose HRHuman, a tuning-free framework for Higher-Resolution Human Image Generation. By leveraging an open-source large human vision model that incorporates rich template knowledge as prior, we first introduce the Prompt Discretization scheme to discretize user-input text prompts, mapping them to image elements and human body parts. Additionally, we implement a Template-guided Prompt Filtering mechanism to align these discretized prompts with regional image semantics, ensuring fine-grained prompt guidance. Extensive experiments demonstrate that HRHuman achieves state-of-the-art performance in human-centeric higher-resolution image generation, significantly addressing both issues of object repetition and structural distortion.